The national reality, the reality of health and health reality of the mother and child - Iparraguirre de Castello, Angelica (2015)
The Reality of Health is an important component of the national reality, therefore, can not be analyzed independently. The national reality conceptualized as a set of problems, material and spiritual resources of a nation to meet their individual and collective needs, it is influenced by a number of physical, political, economic and social factors; factors, which in turn are influencing health reality.